How to do critical discourse analysis: A multimodal introduction - Machin, David; Mayr, Andrea (London Sage, 2013)
Using a multimodal approach graphic, vocal, written How to do Critical Discourse Analysis guides students to an understanding of how language, power and ideology are negotiated in visual communication and media texts, from magazine and advertising, to YouTube and music videos. Authors David Machin and Andrea Mayr draw on discourse analysis, appraisal theory, stylistics and conversation analysis to present a systematic toolkit for doing language and image analysis. Using case studies and examples from a range of traditional and new media content, the book equips students with the necessary tools to analyze and understand the relationship between language, discourse and social practices.